The Contributions of Indigenous Personality and Parenting Style to Life Satisfaction Development in Chinese Adolescents - Li, Mengting (Frontiers in Psychology, 2021)
The present three-wave longitudinal study examined the contributions of indigenous personality traits and parenting style to life satisfaction in Chinese adolescents. Seven hundred and ten junior high school students (Mage = 11.39, SDage= .53; 53.2% girls) were administered self-report measures of personality, parenting styles, and life satisfaction in Grade 6. Data on life satisfaction were collected again in Grades 7 and 8, respectively. Latent growth model analyses indicated that life satisfaction decreased over time. Regression analyses showed that the initial level of global life satisfaction was positively predicted by personality factors of dependability and interpersonal relatedness; the slope of global life satisfaction was positively predicted by personality factors of emotional stability whereas negatively predicted by interpersonal relatedness. The initial levels and slopes of different domains of life satisfaction were predicted by personality factors and parenting styles to different extents. Meanwhile, paternal and maternal parenting styles had different effects on adolescents’ life satisfaction. The study provided valuable information about the contributions of indigenous personality and both paternal and maternal parenting styles to psychological adjustment in the Chinese context. The implications of the findings concerning the associations among personality, parenting styles, and life satisfaction were discussed.